2016
DOI: 10.5152/iao.2016.1776
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Intensity on the Speech Evoked Auditory Late Latency Response in Normal Hearing Individuals

Abstract: OBJECTIVE:Among the stimulus factors, the influence of presentation level is less studied in normal-hearing individuals when using speech stimuli withvarious presentation levels for the auditory late latency response (ALLR). Hence, the present study aimed to explore the Latency-Intensity (L-I) function, i.e., how the latency and amplitude change as a function of intensity using speech stimuli. MATERIALS and METHODS:Speech-evoked ALLR was obtained from 15 normal-hearing individuals. The syllable/ta/ was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 35 publications
1
15
1
Order By: Relevance
“…The decreased latency and increased amplitude of P1 and N1 of the natural speech sound stimulation were not found in this study. Although the change of P1 and N1 were reported to be affected by exogenous factors such as duration and type of stimulus and maturation of auditory system by the previous study [21], that phenomenon was not shown in our study. The latency of P2, N2, and N1-P2 complex and amplitude of P2 showed significant differences between the natural and synthetic speech sound stimuli.…”
Section: Discussioncontrasting
confidence: 88%
“…The decreased latency and increased amplitude of P1 and N1 of the natural speech sound stimulation were not found in this study. Although the change of P1 and N1 were reported to be affected by exogenous factors such as duration and type of stimulus and maturation of auditory system by the previous study [21], that phenomenon was not shown in our study. The latency of P2, N2, and N1-P2 complex and amplitude of P2 showed significant differences between the natural and synthetic speech sound stimuli.…”
Section: Discussioncontrasting
confidence: 88%
“…The positive SU in NH and at T4 and the significant bivariate correlation between SU N and the P2 latency difference between monaural and bimodal LC at T4 affirm this interpretation. Perceived loudness of a binaurally presented stimulus is louder than its monaural presentation (Hawkins et al, 1987), and there is ample evidence, that N1 and P2 amplitudes increase while their latencies decrease concomitant with the intensity of tones or speech syllables presented in quiet and within background noise (Firszt et al, 2002;Martin et al, 2008;Kim et al, 2012;Sharma et al, 2014;Prakash et al, 2016). Thus, results suggest that with a CI experience of about 6 months, the current sample of bimodal listeners could benefit from SU.…”
Section: Aepmentioning
confidence: 76%
“…Furthermore, it is known that amplitudes of the P1, N1 and P2 (exogenous) components are influenced by the physical characteristics of the stimulus 19 , 20 . We speculate that the lower amplitudes presented by the SG individuals with mild to moderate hearing loss occurred because they perceived the stimulus (75 dBnHL) at a lower intensity (dB NS).…”
Section: Discussionmentioning
confidence: 99%